Two new genera of Trachyphloeini with a key to the genera of small terricolous South African Trachyphloeini and Embrithini (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Skuhrovec, Jiří (Zootaxa, 2019)
Two new genera, Barclayanthus Borovec & Skuhrovec, gen. nov. and Janakius Borovec & Skuhrovec, gen. nov., assigned to the tribe Trachyphloeini Lacordaire, 1863, are described for three South African species of weevil: Barclayanthus micros Borovec & Skuhrovec, sp. nov., B. cooteri Borovec & Skuhrovec, sp. nov. and Janakius sylvaticus Borovec & Skuhrovec, sp. nov. All species are illustrated and keyed. The taxonomic status of each of the new genera is discussed, and compared with similar genera of Trachyphloeini and Embrithini Marshall, 1942. A key to known small terricolous South African genera of both Trachyphloeini and Embrithini is included.